Dysrhythmia as a cause of syncope in children without neurological or cardiac morphological abnormalities - (:unkn) unknown (BLACKWELL PUBLISHING ASIA, 2002)
Background : Arrhythmias are among the malignant causes of syncope. This study has been undertaken to determine the relative incidence and significance of dysrhythmia in the pathogenesis of syncope among patients referred to a pediatric cardiology unit. Methods : Between March 1997 and March 1999, 105 consecutive patients (59 female, 46 male) aged 11.5 +/- 3.6 years without neurologic or cardiac morphologic causes were evaluated for at least one episode of syncope. A pediatric cardiologist and a pediatric neurologist evaluated all the patients. Routine chest X-ray, 12-lead electrocardiogram (ECG), electroencephalography (EEG), 24-h Holter monitoring and echocardio-graphy were carried out. When deemed necessary, further tests were undertaken for the cases of syncope which were unexplained by routine tests. Results : The cause of syncope was identified as vasovagal in 25.7% (n = 27) and related to dysrhythmia in 30.5% (n = 32). The cause was migraine-associated syncope in two children, psychogenic syncope in three children and orthostatic hypotension in one patient. The cause was unknown in 36.2% (n = 38). Conclusion : We conclude that dysrhythmia is a significant and frequent cause in children referred to pediatric cardiology units. The combination of ECG, Holter monitoring, electrophysiologic study, transtelephonic ECG and head-up tilt test can identify the underlying cause of syncope in as many as 58% of these patients that present with syncope.
Keywords: childhood; dysrhythmia; syncope; TILT-TABLE TEST; UNEXPLAINED SYNCOPE; HEART-DISEASE; REPRODUCIBILITY; CHILDHOOD